Influence of continuous flow bead-milling process parameters on sulfur curative and its performance for elastomeric rubber composites - Omar, Mohamad Firdaus; Ali, Fathilah; Jami, Mohammed Saedi; Azmi, Azlin Suhaida; Ahmad, Farah; Marzuki, Mohd Zahid (Kulliyyah of Engineering, 2023)
Bead-milling is an eco-friendly and feasible method for physical modification of materials that has been extensively used in many industrial applications impacting on particle size and overall products’ performance. While previous studies explored various bead-milling parameters in different applications, limited research conducted on sulfur curative dispersion, necessitating a thorough investigation of its performance after bead-milling is applied. The primary objectives of the present study were to explore the influence of bead-milling process parameters, particularly rotational speed and flow rate on the sulfur curative dispersion characteristics and to analyze its behavior within the rubber elastomer matrix. Taguchi’s L9 orthogonal array experimental design was employed to identify the optimal rotational speed and flow rate of a 60-L bead-milling machine on the sulfur curative dispersion. It was found that higher rotational speed (800 rpm) and lower flow rate (350 L/h) of the bead-milling process resultedin smaller sulfur particle sizes, leading to slight improvement on tensile strength of the rubber elastomerand hindered the formation of severe sulfur crystals on the casted rubber elastomer –and vice versa. This research providesvaluable insights to determine the ideal bead-milling process for sulfur curative, enhancing the mechanical properties and overall performance of elastomeric rubber composites.